(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Marriage is often legally recognized union between people. This study compare marital satisfaction and general well-being of married individuals. Relationship between marital satisfaction and general well-being related each other. Total 196 participants participated in the study. Married individuals were participated in the study. Positive and significant relation exists between marital satisfaction and well-being.